Selected readings in econometrics from Econometrica - Hooper, John W.; Nerlove, Marc. (Cambridge, Mass. : M.I.T. Press, 1970)
This volume presents in a convenient form certain articles originally published in Econometrica, which has played a major role in the development of econometrics. It is hoped that this collection of representative articles will prove useful to students and professional practitioners of econometrics as a reference work, and that it will serve to suggest the growth, development, and changing emphasis of the subject over the past thirty years.
Includes bibliographical references and index.
rpm 06/08/2017
Loans
Keywords: Econometrics